Principles of operations management. - Heizer, Jay H., 1935-; Render, Barry, 1946- (Boston : Pearson, 2011)
Principles of Operations Management presents a broad introduction to the field of operations in a realistic and practical manner, while offering the largest and most diverse collection of problems on the market. Operations and Productivity; Operations Strategy in a Global Environment; Project Management; Forecasting; Design of Goods and Services; Managing Quality; Process Strategy; Location Strategies; Layout Strategies; Human Resources, Job Design, and Work Measurement; Supply Chain Management; Inventory Management; Aggregate Planning; Material Requirements Planning (MRP) and ERP; Short-Term Scheduling; Just-in-Time and Lean Operations; Maintenance and Reliability For anyone interested in operations management and gaining the fundamental working knowledge of a firm.